The Expression of Calprotectin and Factors in TLR4/NF-κB/MyD88 Pathway in Patients with Idiopathic Acute Anterior Uveitis. (3rd October 2019) - Song, Guoxiang; Huang, Jinxian; Deng, Yaling; Liang, Zhangyi; Lin, Yannan
ABSTRACT: Purpose : The purpose of the article is to investigate the contribution of calprotectin and factors in toll-like receptor 4/nuclear factor-κB/myeloid differentiation factor 88 (TLR4/NF-κB/MyD88) pathway in patients with idiopathic acute anterior uveitis (IAAU). Methods : In total, 72 patients with IAAU and 56 healthy individuals were enrolled. Serum calprotectin, TLR-4, and MyD88 were determined. Best-corrected visual acuity, uveitis activity grading, and macular thickness measured by optical coherence tomography were performed. Results : Serum calprotectin, TLR4, and MyD88 levels were higher in IAAU group than those in healthy individuals. Serum calprotectin level was positively correlated with uveitis activity grading and macular thickness. Receiver operating characteristic curve analysis showed serum calprotectin had larger area under curve than serum TLR4 and MyD88. Conclusions : The calprotectin and TLR4/NF-κB/MyD88 signal might contribute to the pathogenesis of IAAU and serum calprotectin might be a specific biomarker for the measurement of ocular inflammation in IAAU.